跨領域素養導向課程設計工作坊之構思與實踐 Ideation and Practice of Interdisciplinary Competence-Based Curriculum Workshop - 陳佩英 Pei-Ying Chen (Higher Education Foundation, 2018)
本研究由跨領域素養導向課程之實務設計切入，針對教師團隊所發展的課程增能模式，說明如何經由課程設計的「深學習」流程，協助其他教師經驗並習得跨領域素養的課程與教學專業知能，進而轉化新課綱的課程目標。深學習意指組構於核心的價值理念、學習流程和經驗知識積累之協力探究的四層次連結與循環，進行教師專業知能提升的系統轉換。經1年30多場工作坊的辦理，約八成學員非常同意工作坊的學習助益。深學習的核心為新課綱的終身學習之核心素養能力；第二層是工作坊課程的設計理念與流程；第三層為教師課程與教學專業知能的發展與積累；最後一層為促進教師嘗試跨領域素養課程發展與試行，並持續協力探究的增能循環。 This paper takes a pragmatic approach, aiming to display the cyclical process of collaborative inquiry that facilitates teachers to acquire understanding of interdisciplinary competence-based curriculum and instruction provided by the "deep learning" process of curriculum designing. Based on this understanding, teachers could further transform the goal of the new curriculum. Deep learning takes place in the cycle of the core value, the learning process, and the collaborative inquiry on accumulation of experiential knowledge. It also aims to a systematic transformation of teacher's proficiency. As 30 workshops taking places in a single year, about 80% of participator agreed its benefits. The core of deep learning is the life-long learning competence highlighted in the new curriculum, the second round is idea and process of the workshop curriculum designing, the third round is the development and accumulation of teacher's proficiency, the last round is the collaborative inquiry which inspires teachers on the development and practice of interdisciplinary competence-based curriculum.